Farmers' market shopping and dietary behaviours among Supplemental Nutrition Assistance Program participants. Issue 13 (21st April 2015) - Jilcott Pitts, Stephanie B; Wu, Qiang; Demarest, Chelsea L; Dixon, Crystal E; Dortche, Ciarra JM; Bullock, Sally L; McGuirt, Jared; Ward, Rachel; Ammerman, Alice S
Abstract: Objective: Because farmers' markets include a variety of fruits and vegetables, shopping at farmers' markets would likely improve diet quality among low-income consumers, as well as promote sustainable direct farm-to-consumer business models. However, not much is known about how to promote farmers' market shopping among low-income consumers. Therefore, the purpose of the present paper was to examine barriers to and facilitators of shopping at farmers' markets and associations between shopping at farmers' markets and self-reported dietary behaviours (fruit and vegetable, sugar-sweetened beverage and fast-food consumption) and BMI. Design: Cross-sectional analyses of associations between farmers' market shopping frequency, awareness of markets, access to markets, dietary behaviours and BMI. Setting: Department of Social Services, Pitt County, eastern North Carolina, USA. Subjects: Between April and July 2013, Supplemental Nutrition Assistance Program (SNAP) participants ( n 205) completed a quantitative survey. Results: Barriers to shopping at farmers' markets included does not accept SNAP/electronic benefit transfer, out of the way and lack of transportation. Farmers' market shopping was associated with awareness of farmers' markets (estimate =0·18 (se 0·04), P <0·001). Fruit and vegetable consumption was positively associated with farmers' market shopping (estimate =1·06 (se 0·32), P =0·001). Conclusions: Our study is one of the first to examine SNAP participants' farmers' market shopping, distance to farmers' markets and dietary behaviours. Barriers to shopping at farmers' markets and increasing awareness of existing markets should be addressed in future interventions to increase SNAP participants' use of farmers' markets, ultimately improving diet quality in this high-risk group.